Hermitian metrics with (anti-)self-dual Riemann tensor - Leonid Krivonosov; Vyacheslav Luk'yanov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2021)
Equations of (anti-)self-duality for the components of the LeviCivita connection of the Hermitian positive definite metric (not for the Riemann tensor) are compiled. With this well-known method, a simpler system of partial differential equations is obtained, which implies the (anti-)self-duality of the Riemann tensor. This system is of the 1st order, while the (anti-)self-duality conditions of the Riemann tensor are expressed by equations of the 2nd order. However, this method can obtain only particular solutions of the (anti-)self-duality equations of the Riemann tensor. The constructed equations turned out to be significantly different in the self-dual and anti-self-dual cases. In the case of self-duality, the equations are divided into three classes, for each of which a general solution is found. In the anti-self-dual case, we did not find the general solution, but gave two series of particular solutions. The connection between our solutions and Kähler metrics is shown. In the case of the (anti-)self-duality of the LeviCivita connection for the Hermitian metric, a general form of parallel almost complex metric-preserving structures is obtained. These structures are all torsion free. For an arbitrary positive definite 4-metric, a general form of almost complex structures preserving this metric is found.